Endenich near Bonn - Heath, Charles, 1785-1848 (engraver):::Creator::::::::::::; Stanfield, Clarkson Frederick, 1783-1867 (artist):::Contributor:::::::::::: (London; Longman & Co., 2020)
Steel engraving of Endenich near Bonn